Prenatal diagnosis of harlequin ichthyosis: a case report - Mudunuri Vijayakumari; Desai. Kamalakar Reddy; Madhavilatha Routhu; Manasvi Vuchuru; Nallamilli Sunitha Reddy (Korean Society of Obstetrics and Gynecology, 2020)
Harlequin ichthyosis (HI) is a rare and severe form of ichthyosis and is characterized by thickened, hard, armor-like plates of skin that cover the entire body. This disease is caused by mutations in the adenosine triphosphate-binding cassette transporter protein A12 gene, and the pattern of inheritance is autosomal recessive. Prenatal sonographic diagnosis of HI has not been frequently reported. Here, we report a case of HI detected at 28 weeks of gestation and discuss with the sonographic findings and a brief review of literature. The diagnosis was reached mainly based on 2-dimensional and 3-dimensional ultrasound findings. Three-dimensional ultrasound applications help recognize facial morphology, and thus, greatly contributes to prenatal diagnoses.